FINANCIAL INFORMATION SYSTEMS MUHAMMADIYAH BOARDING SCHOOL SABILIL MUTTAQIEN GISTING - Rinawati, Rinawati; Maghfiroh, Wasingatul (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
Muhammadiyah Islamic Boarding School Sabilil Muttaqien was established in 2000 and is the first Muhammadiyah Islamic Boarding School in Tanggamus. Financial management at the Muhammadiyah Sabilil Muttaqien Islamic Boarding School still faces various problems. In addition, financial management at the boarding school met with obstacles relating to the budget, accounting, administrative arrangements, allocation and development needs of the pesantren as well as in the process of daily activities. This is because in Islamic boarding schools still use a very simple financial management system, not yet using an integrated financial system. For this reason, researchers conducted research on financial information systems at Muhammadiyah Islamic Boarding School Sabilil Muttaqien and made a financial application using the visual basic programming language and the MySQL database. Data collection methods conducted by researchers are by observation, interviews, and literature study in addition to that the writer also uses the waterfall method as a method of developing the system. The purpose of this research is to design a system that can be used to record activities and financial income and expenditure quickly and easily as well as facilitate financial staff in preparing financial reports. From the results of this research, the financial information system can be accessed by the treasurer through a desktop application that can speed up the process of recording activities and financial income and expenditure easily and quickly and can minimize errors in inputting data carried out conventionally and optimize data security.